Characterization of Health Beneficial Components in Discarded Leaves of Three Escarole (Cichorium endivia L.) Cultivar and Study of Their Antioxidant and Anti-Inflammatory Activities - Giuliana Donadio; Maria Laura Bellone; Francesca Mensitieri; Valentina Parisi; Valentina Santoro; Maria Vitiello; Fabrizio Dal Piaz; Nunziatina De Tommasi (MDPI AG, 2023)
Plants of genus Cichorium (Asteraceae) can be used as vegetables with higher nutritional value and as medicinal plants. This genus has beneficial properties owing to the presence of a number of specialized metabolites such as alkaloids, sesquiterpene lactones, coumarins, unsaturated fatty acids, flavonoids, saponins, and tannins. Cichorium endivia L., known as escarole, has achieved a common food status due to its nutritionary value, bitter taste, and the presence of healthy components, and is eaten cooked or raw in salads. Presently, wastes derived from the horticultural crops supply chain are generated in very large amounts. Vegetable waste comprises the discarded leaves of food sources produced during collection, handling, transportation, and processing. The external leaves of Cichorium endivia L. are a horticultural crop that is discarded. In this work, the phytochemical profile, antioxidant, and anti-inflammatory activities of hydroalcoholic extract obtained from discarded leaves of three cultivars of escarole (C. endivia var. crispum 'Capriccio', C. endivia var. latifolium 'Performance' and 'Leonida') typical horticultural crop of the Campania region were investigated. In order to describe a metabolite profile of C. endivia cultivars, the extracts were analysed by HR/ESI/Qexactive/MS/MS and NMR. The careful analysis of the accurate masses, the ESI/MS spectra, and the 1H NMR chemical shifts allowed for the identification of small molecules belonging to phenolic, flavonoid, sesquiterpene, amino acids, and unsaturated fatty acid classes. In addition, the antioxidant potential of the extracts was evaluated using cell-free and cell-based assays, as well as their cytotoxic and anti-inflammatory activity. All the extracts showed similar radical-scavenging ability while significant differences between the three investigated cultivars emerged in the cell-based assays. The obtained data were ascribed to the content of polyphenols and sesquiterpenes in the extracts. Accordingly, C. endivia by-products can be deemed an interesting material for healthy product formulations.